علاقة شكيب ارسلان بالحركات الوطنية المغاربية - عاشور، حمزة, هبهوبة، فوزي (جامعة الوادي university of Eloued, 2021)
الملخص: يكتسي موضوع علاقة شكيب أرسلان بالحركات الوطنية المغاربية أهمية كبيرة, حيث نهدف من خلال هذه الدراسة إلى تسليط الضوء على السيرة الذاتية للأمير شكيب أرسلان والتعرف على رحلاته وانجازاته, ومن ثم نتطرق إلى نضالات الأمير في المغرب العربي الكبير وعلاقاته مع رموز الحركات الوطنية المغاربية ومواقف الاستعمار الفرنسي والإسباني من نشاطه في هاته الدول. Résumé : فرنسية أو انجلزية The subject of Chakib Arslan’s relationship with the Maghreb national movements is of great importance, as we aim through this study to shed light on the biography of Emir Chakib Arslan and learn about his travels and achievements, and then we touch on the struggles of the Emir in the Great Maghreb and his relations with the symbols of the Maghreb national movements and the positions of French colonialism The Spaniard is active in these countries.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: شكيب أرسلان، الحركات الوطنية المغاربية; Chakib Arslan, Maghreb National Movements; Chakib Arslan, Mouvements nationaux maghrébins